Developing Arabic Language Textbooks Based on Religious Moderation in Madrasah - Andi Arif Pamessangi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to construct an Arabic Language Textbook based on Religious Moderation at Madrasah Ibtidaiyah in Palopo City and measure the book's effectiveness in improving students' Arabic language skills. This study implemented Research and Development using the model of ADDIE. The data was collected by observation, interviews, questionnaires, and documentation. The Arabic Language Learning Book based on Religious Moderation at Madrasah Ibtidaiyah in Palopo City was designed by considering the theory of developing Arabic language learning books for elementary school children and non-native speakers and based on the results of the analysis of the needs of Ibtidaiyah madrasa students in Palopo City. The test results show that the designed book can help improve students' Arabic language skills. In addition to enhancing students' Arabic language skills, the prepared textbooks are very helpful in increasing students' understanding of religious moderation. This research has implications for the importance of developing teaching materials carried out by teachers by taking into account the socio-cultural context of the community and the dynamics of the times so that the teaching materials made can provide maximum results.